Impact possibility of hedgerows on plant protection and on the yield of winter wheat - Szarvas, Péter (Acta Agraria Debreceniensis, 2006)
Agricultural hedgerows have various impacts on the surrounding cultivated area and on the landscape. They serve as a windbreak, help manage humidity and precipitation, and are also sources of plant species richness which can contribute to the animal biodiversity. One of their beneficial effects is the yield improvement of agricultural crops. Our investigation tries to prove this hypothesis in Hungarian circumstances in the case of several winter wheat fields near Debrecen. Regarding the results, it seems that the majority of data supports the relevant, mainly German and Austrian information, but in some cases, the correlation has not been significant.